Pembukaan Kantor Perwakilan Diplomatik Suatu Negara oleh Maroko di Wilayah Sahara Barat Berdasarkan The Montevideo Convention (On The Right and Duties of States) 1933 - Bilhikam, Muhamad Yasirni; Putra, Hilton Tarnama; Jumena, Masnana (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
The opening of a diplomatic representative office is a series of diplomatic activities carried out by the receiving country for facilitation of the sending country. The author in his research uses a framework of thinking, as follows: Non-intervention Principles and State Sovereignty Theory. In compiling the identification of the problem in this first research, How was the Opening of a Diplomatic Representative Office by Morocco in the Western Sahara Region based on The Montevideo Convention (The Right and Duties of State) 1933? Then second, what are the settlement steps for the Opening of a Diplomatic Representative Office by Morocco in the Western Sahara Region based on the International Dispute Settlement Law? This research method uses the Juridical-Normative method, the approach uses the Historicalcal Approach and the Case Approach. The results of this research are: first, the opening of a diplomatic representative office of a country by Morocco in the Western Sahara Region based on The Montevideo Convention on The Right and Duties of States is an act that is strictly prohibited because it violates articles 8 and 9 which contain elements of intervention and damage the sovereignty of a country. country. then the second, regarding the resolution of the conflict. The United Nation has made several attempts through the path of peace, but these have not found a resolution to the conflict. So it is necessary to take legal action as an ultimum remedium, namely by suing related to the actions of Morocco which carried out the inauguration of a diplomatic representative office of a country in the Western Sahara region as a result of having intervened in a country's policy.